2018
DOI: 10.3390/su10072167
|View full text |Cite
|
Sign up to set email alerts
|

Creating Smart Energy Cities for Sustainability through Project Implementation: A Case Study of Bolzano, Italy

Abstract: Globally, cities are experiencing an unprecedented socio-economic, demographic, and environmental transition that brings with it negative environmental externalities, such as climate change and environmental degradation. Smart energy city (SEC) has emerged as the latest urban development strategy in European countries. It can vastly accelerate cities' decarbonisation efforts, which can have several co-benefits. Capitalising on advances in information and communication technologies (ICT), various SEC projects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…A previous study by Hunter et al [55] identified four sustainable development principles: (1) Integration; (2) implementing; (3) equity (intra-generational, procedural, and inter-generational); and (4) scalability and replicability ( Figure 4). Based on Figure 5, the LCC components identified were categorized and integrated into the four core endogenous sustainable development principles [55].…”
Section: Assimilating the Components Of Lcc In The Core Sustainable Dmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study by Hunter et al [55] identified four sustainable development principles: (1) Integration; (2) implementing; (3) equity (intra-generational, procedural, and inter-generational); and (4) scalability and replicability ( Figure 4). Based on Figure 5, the LCC components identified were categorized and integrated into the four core endogenous sustainable development principles [55].…”
Section: Assimilating the Components Of Lcc In The Core Sustainable Dmentioning
confidence: 99%
“…A previous study by Hunter et al [55] identified four sustainable development principles: (1) Integration; (2) implementing; (3) equity (intra-generational, procedural, and inter-generational); and (4) scalability and replicability ( Figure 4). Based on Figure 5, the LCC components identified were categorized and integrated into the four core endogenous sustainable development principles [55]. The integration principle posits that the quest for sustainability should balance environmental, societal, economic, and governance considerations, and their interdependencies that are intrinsic for improving citizens' quality of life among other co-benefits.…”
Section: Assimilating the Components Of Lcc In The Core Sustainable Dmentioning
confidence: 99%
See 3 more Smart Citations